Theoretical evaluation of dynamic creep modulus of bituminous concrete and comparison with experimental results - Shakor R Badaruddin, (1995)
Knowledge of bituminous creep modulus is very important to.fully characterize a premix. Conventional methods to determine it involve elaborate laboratory procedure requiring specialized equipment and trained personnel. Theoretical methods to calculate dynamic creep modulus (E*) have been available but very little comparison between theoretical and laboratory results are available in the literature. A study was carried out to determine the laboratory E* values of a set of field cores. The same cores were then analyzed for their physical properties such as penetration, viscosity and air-void content which were used as input for the determination of the theoretical E*. A comparison was then made between the laboratory and theoretical E* values in graphical plots which showed agreement within a factor two. In many analysis, this is close enough given the inherent variability within a premix. Thus, in cases where laboratory E* could not be performed, a quick estimate could be obtained using the method shown in this study